Postazacitidine clone size predicts long-term outcome of patients with myelodysplastic syndromes and related myeloid neoplasms - Nannya, Yasuhito; Tobiasson, Magnus; Sato, Shinya; Bernard, Elsa; Ohtake, Shigeki; Takeda, June; Creignou, Maria; Zhao, Lanying; Kusakabe, Manabu; Shibata, Yuhei; Nakamura, Nobuhiko; Watanabe, Mizuki; et al. (Blood advances, 2023)
•Major clone sizes in posttreatment samples are strongly correlated with clinical response.•Inclusion of posttreatment clone size into the prognostic model allows better prognostication for MDS cases treated with azacitidine. [Display omitted] Azacitidine is a mainstay of therapy for myelodysplastic syndrome (MDS)–related diseases. The purpose of our study is to elucidate the effect of gene mutations on hematological response and overall survival (OS), particularly focusing on their posttreatment clone size. We enrolled a total of 449 patients with MDS or related myeloid neoplasms. They were analyzed for gene mutations in pretreatment (n = 449) and posttreatment (n = 289) bone marrow samples using targeted-capture sequencing to assess the impact of gene mutations and their posttreatment clone size on treatment outcomes. In Cox proportional hazard modeling, multihit TP53 mutation (hazard ratio [HR], 2.03; 95% confidence interval [CI], 1.42-2.91; P < .001), EZH2 mutation (HR, 1.71; 95% CI, 1.14-2.54; P = .009), and DDX41 mutation (HR, 0.33; 95% CI, 0.17-0.62; P < .001), together with age, high-risk karyotypes, low platelets, and high blast counts, independently predicted OS. Posttreatment clone size accounting for all drivers significantly correlated with International Working Group (IWG) response (P < .001, using trend test), except for that of DDX41-mutated clones, which did not predict IWG response. Combined, IWG response and posttreatment clone size further improved the prediction of the original model and even that of a recently proposed molecular prediction model, the molecular International Prognostic Scoring System (IPSS-M; c-index, 0.653 vs 0.688; P < .001, using likelihood ratio test). In conclusion, evaluation of posttreatment clone size, together with the pretreatment mutational profile as well as the IWG response play a role in better prognostication of azacitidine-treated patients with myelodysplasia.